The Atacama Cosmology Telescope: SZ-based masses and dust emission from IR-selected cluster candidates in the SHELA survey. Issue 3 (25th January 2021) - Fuzia, Brittany J; Kawinwanichakij, Lalitwadee; Mehrtens, Nicola; Aiola, Simone; Battaglia, Nicholas; Ciardullo, Robin; Devlin, Mark; Finkelstein, Steven L; Gralla, Megan; Hilton, Matt; Huffenberger, Kevin M; Hughes, John P; et al.
ABSTRACT: We examine the stacked thermal Sunyaev–Zel'dovich (SZ) signals for a sample of galaxy group and cluster candidates from the 24 deg 2 infrared Spitzer -HETDEX Exploratory Large Area (SHELA) survey. We identify the objects in combination with optical data using the redMaPPer algorithm, and divide them into three richness bins (λ in 10–20, 20–30, and 30–76 with average photometric redshifts of 0.80, 0.73, and 0.70, respectively). All richness bins show evidence for dust emission, which we fit using stacked profiles from Herschel Stripe 82 data. We fit for synchrotron emission using stacked profiles created by binning source fluxes from NRAO VLA Sky Survey data. We can confidently detect the SZ decrement only in the highest richness bin, finding M SZ, 500 = $8.7^{+1.7}_{-1.3} × 10^{13}\, M_\odot$ . Neglecting the correction for dust and synchrotron depresses the inferred mass by 26 per cent, indicating a partial fill-in of the SZ decrement from dust and synchrotron emission. We compare our corrected SZ masses to two redMaPPer mass–richness scaling relations and find that the SZ mass is lower than predicted by the richness. For the lower richness bins, mass bias factors as low as 1 − b = 0.6 are not enough to bring the mass limits into agreement. We discuss possible explanations for this discrepancy. The SHELA richnesses may differ from previous richness measurements due to the inclusion of infrared data in redMaPPer. To connect the SZ signal to the mass, we use a universal gas pressure profile that is calibrated to massive clusters at low redshift. It may not be applicable to our lower mass, higher redshift sample.